Students’ Accuracy In English Speaking Skill Through Word Stress In Fifth-Grade Students At Sds 117 Islam Intergrated Adnani - Nur Fadilah Fadilah; Ririn Arianti; Sarah Adelina; Citra Tiurnida Panggabean (Advances In Education Journal, 2025)
This study aims to analyze the effect of word stress mastery on the English speaking accuracy of fifth-grade students at SDs 117 Islam Terpadu Adnani. With a descriptive qualitative approach and based on Chomsky's Competence and Performance theory, this study involved 25 students selected through a total sampling technique. Data were collected through observation, interviews, and documentation. The results of the study indicate that students' understanding of word stress is not fully in line with their pronunciation abilities. The main difficulties include the lack of exposure to accurate pronunciation models and the complexity of word stress rules. This study concludes that word stress mastery has a significant effect on students' English speaking accuracy.